Hybrid EUV Resists with Mixed Organic Shells: A Simple Preparation Method. Issue 38 (16th October 2019) - Wu, Lianjia; Liu, Jeremy; Vockenhuber, Michaela; Ekinci, Yasin; Castellanos, Sonia
Abstract : Metal‐containing molecular hybrid compounds, such as metal oxoclusters (MOCs), are promising materials for extreme ultraviolet (EUV) lithography. The solubility, processability, and reactivity towards EUV photons in these compounds are mostly determined by the composition of their organic shells. Therefore, gaining molecular control on the composition of the shell is crucial to tune their lithographic performance of sensitivity, resolution, and line‐edge roughness. In this work, a new method to prepare MOCs that feature two types of carboxylate ligands is presented. In this method, amine‐functionalized resins are used for the purification step. By using this protocol, Ti‐ and Zr‐based MOCs with mixed‐ligands organic shells were synthesized. The new compounds showed clear differences in the processability and sensitivity as EUV resists compared to their analogues featuring only one type of ligand. The results validate this new synthetic approach for the preparation of custom‐made EUV resists towards better lithographic performance. Abstract : Ligand exchange reactions followed by basic resin treatment allow to synthesize Zr‐ and Ti‐based metal oxoclusters with mixed organic shells featuring methacrylate and pivalate ligands. The performance of these new photoresist materials in extreme ultraviolet lithography is affected by the number of methacrylate ligands in their organic shell.